Model ADDIE Berbasis Kearifan Lokal Ende-Lio untuk Meningkatkan Kualitas Perkuliahan Desain Pembelajaran IPA - Nining Sar’iyyah; Adi Neneng Abdullah; Chatarina Novianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The study aims to improve the quality of learning science in designing at PGSD students of Universitas Flores through ADDIE model with local wisdom based. The research was a classroom action research with some steps such as planning, action, observation and reflection. The data included science learning product with Ende-Lio local wisdom based, students activities and creativity. The result was that the product evaluation in cycle I reached 70%. In cycle II, the percentage improved for 92%. The activities and creativity were also improved. In conclusion, ADDIE model with Ende-Lio local wisdon based can improve students ability in designing science learning. Keywords: ADDIE model, local wisdom Ende-Lio, teaching design.